2015
DOI: 10.2474/trol.10.183
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Adsorbed Albumin Film on CoCrMo Alloy under <I>In-situ</I> Observation

Abstract: The protein film adsorbed on joint prosthesis material affects tribological property. It is expected that optimum protein film structure could improve friction and wear of joint prosthesis materials. Therefore, it is important to understand and to clarify the effect of protein film on tribological property. In the rubbing combination of ultra-high molecular weight polyethylene (UHMWPE) and CoCrMo alloy, the adsorption behavior of bovine serum albumin (BSA) and its effect on frictional property during friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…4,10,12 Most of the studies found are concerned with adsorption and desorption of proteins in different kinematic conditions and film thickness in different pH, buffer, and concentration of proteins. 7,13,14,[16][17][18][19] Frictional coefficients, frictional force, shear force, wear measurement, boundary lubrication, surface geometry, rheology of various constituents are also considered in connection with proteins and other SF components to explore the knowledge in this area. 2,3,8,14,15,19,23 To take into account the mechanical and chemical environment of human synovial joint, the viscosity of various modal fluids and wettability of various surface materials were also considered 4,[15][16][17]23 with respect to their duration in time and under varying temperature and pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,10,12 Most of the studies found are concerned with adsorption and desorption of proteins in different kinematic conditions and film thickness in different pH, buffer, and concentration of proteins. 7,13,14,[16][17][18][19] Frictional coefficients, frictional force, shear force, wear measurement, boundary lubrication, surface geometry, rheology of various constituents are also considered in connection with proteins and other SF components to explore the knowledge in this area. 2,3,8,14,15,19,23 To take into account the mechanical and chemical environment of human synovial joint, the viscosity of various modal fluids and wettability of various surface materials were also considered 4,[15][16][17]23 with respect to their duration in time and under varying temperature and pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Nakashima et al 14 studied the adsorption of BSA through measurement of friction force and electric potential under open circuit potential condition in the rubbing combination of ultrahigh molecular weight polyethylene and CoCrMo alloy. The results show the onset of BSA desorption at first rubbing with the gradual decline of desorption.…”
Section: Composition Of Formed Protein Filmsmentioning
confidence: 99%
“…Unexpectedly, the addition of HA did not affect the lubrication performance provided by PC layers according to Lin et al 33 SA is the most common protein in synovial fluid, 34 but its lubrication role remains controversial until now. 29,35 For example, Yoneyama et al 29 concluded that SA functioned as a lubrication role to reduce friction, while Nakashima et al 35 found that SA worsened the friction and wear of joint prosthesis materials.…”
Section: Introductionmentioning
confidence: 99%
“…Using real-time information about the adsorption and desorption of proteins, it was disclosed that during rubbing, the BSA film is reconstructed on the Co-Cr-Mo surface by shear force. By acquiring shear force, the adsorbed film becomes a strong, stable and optimally adapted structure [8]. Electrochemical corrosion resistance is a vital factor in the biocompatibility of metals.…”
Section: Introductionmentioning
confidence: 99%